Arthroscopic-assisted uniportal spinal surgery for treatment of lumbar burst fractures complicated with neurological symptoms: a case report - Hai-Wei Chen; Zhi-Qiang Wang; Peng-Ju Jing; Dong-Hong Ma; Wen-Bo Wang; En Song; Pei-Wu Li; Peng Cheng (Journal of International Medical Research)
Lumbar burst fractures account for 21% to 58% of all thoracolumbar fractures. L5 lumbar burst fractures are rare, comprising 1.2% of spinal burst fractures. This report discusses the optimal treatment for an adolescent with an L5 lumbar burst fracture and neurological symptoms caused by a high-fall injury, which involved surgical decompression and spinal fixation. Complete decompression and fixation of the L5 lumbar burst fracture, complicated by neurological symptoms, were achieved using arthroscopic-assisted uniportal spinal surgery (AUSS) combined with percutaneous pedicle screw fixation (PPSF). The AUSS approach, used alongside PPSF, significantly improved the vertebral canal occupation rate, increased the anterior edge height ratio of the damaged vertebra, and alleviated the lower back pain and nerve root symptoms postoperatively. AUSS combined with PPSF is a minimally invasive technique for treating lumbar burst fractures, effectively relieving compression of the vertebral canal and nerves caused by fracture fragments.